Effect of rehabilitation program on improvement of muscle strength and accuracy and its relationship to the level of achievement of the air pistol for special needs of patients with acute elbow - Enad, Liqaa Ali; Mohammed, Raghdaa Fouad (International Journal of Psychosocial Rehabilitation, 2020)
The scientific development included all life facilities and entered all fields, including the field of sports rehabilitation for the disabled, and new methods of rehabilitation or developing old methods appeared every day in a way that was compatible with the requirements of new life and the extent of progress achieved in it, so it became necessary to find easy and comfortable ways to provide improvement and development for the disabled. Lateral condyle inflammation of the elbow joint and the causes of injury and the importance of research lies in the use of well-established and moving therapeutic exercises through setting up a rehabilitation program that helps the athlete to improve tangible in his condition as well as to achieve good development in a record time, so the researcher decided to develop a program to rehabilitate the injured elbow joint and increase his ability to Endurance and the development of muscle strength and accuracy of the archer and the goal of the research is to prepare a rehabilitative program using an ultrasound device and therapeutic exercises for the injured elbow joint for air gun players (10 meters) for people with special needs and to identify the effect of the prepared program on improving muscle strength, accuracy and the level of achievement of air pistol players (10) Meters for people with special needs. To achieve the goal of the research, the researcher assumed that there are differences of opinion Statistical significance between the results of the pre and post -tests in muscle strength, accuracy and level of achievement for the research group, and statistically significant differences between the results of the post tests in muscle strength, accuracy and level of achievement of the group. As for the research method, the researcher used the experimental method for its suitability and the nature of the problem. Of the players of the national team for the effectiveness of air weapon shooting (10) meters for the air pistol for people with special needs and the five injured in the lateralcondyle of the elbow joint and the number (5) were injured. As for the conclusions, the rehabilitation program had a positive effect on the improvement of the brutal bite in the injured tennis elbow, muscle strength and accuracy as well as It has a positive effect on improving the level of achievement with the air pistol for those with special needs and the recommendations are to adopt the rehabilitative approach prepared by the researcher that includes therapeutic exercises with an ultrasound device for its effective effect in treating injury as well as improving muscle strength, accuracy and the level of achievement with the air pistol 10m for people with special needs and the need Pay attention to exercise use Treatment methods aimed at strengthening the injured muscles of athletesIn addition to the interest of the player and coach about the injury at the time of its occurrence with regard to treatment and the use of the necessary means and giving it sufficient time to recover before returning to the stadiums to avoid repeated and chronic injuries.